Processo de elaboração de uma matriz curricular : especificidades do ensino e aprendizagem de língua espanhola no CEL-São Carlos - Oliveira, Geandro de (2015)
This research aims to investigate the process of construction and implementation of the Spanish language Course Curriculum at a Language Center located in the countryside of São Paulo. Therefore, as observed in the teaching-learning process in all years of school it is proposed examination of the entered students in the Spanish course. In this way, a special focus will be given in two important issues: the ways in which managers and teachers form the new classes of languages and which tools are used to evaluate if a student is prepared or not for next levels. For this, it will be used documents as the Resolution 81/2009 and 44/2014, in order to investigate the theoretical basis of curriculum proposal of the Spanish language teaching, also the comparison between the skills and abilities of PCN - EF and MS (2000), the OCN (2006) and the Common European Framework of Reference (2001). It will also be essential the concept of curriculum discussion according to Serrani (2005), Goodson (1995) and Sacristán (2000).